Study on the anti-inflamatory activity of baccharis lanceolata kunth extracts in laboratoy animals - Jurupe, Hilda (1995)
Watery, ethanolic and di-chloromethane extracts made of leafs of Baccharis lanceolata, were assayed by their possible anti-inflamatory activity. Extracts were given oral and topically to rats with plantar edema produced by carragenin or to rats with auricular edema induced by croton oil, respectively. This effect was dosis-dependent and the major effect anti-edema was the dichloromethane extract which produced 68% of inhibition in both patterns.